CONCEPT OF MEASURING THE ECONOMIC RISK IN THE FORM OF RISK CLASSES MODEL - Katarzyna Chłapek; Ewelina Wawryk-Gawda (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2015)
Business risk, due to its complexity is the subject of extensive research, also with respect to measurement. The need to develop a concept of measuring the economic risks inspired the research, the results of which are included in this article. The risk classes model based on international trends and methodology used in the insurance business, allows for the assessment of the level of security of the company.